AB0552 The clinical and laboratory features of antiphospholipid antibody positive patients with or without systemic lupus erythematosus. (12th June 2018) - Yazici, A.; Omma, A.; Yilmaz, S.; Yavuz, S.; Ayar, K.; Kasapoglu, E.; Kisacik, B.; Cefle, A.; Erkan, D.
Abstract : Background: A multicenter antiphospholipid antibody (aPL) clinical database was created in 2016 with the pariticipation of six rheumatology centres around the country. The purpose has been to better define aPL-related clinical manifestations and management strategies; and also to establish a resource for future clinical studies. Objectives: In this first analysis, we compared the clinical and laboratory features of aPL-positive patients with and without systemic lupus erythematosus (SLE). Methods: The demographic, clinical, laboratory, treatment characteristics of the aPL-positive patients with/without other systemic autoimmune diseases (SAID) are recorded at enrollment according to a predefined protocol. The inclusion criteria are positive aPL (lupus anticoagulant test [LA], anticardiolipin antibody [aCL], and/or anti β2 -glycoprotein-I antibody [aβ2 GPI]) based on the Updated Sapporo Antiphospholipid Syndrome (APS) Classification Criteria at least twice within one year prior to enrolment. 1, 2 For the purpose of this analysis, we only included aPL-positive patients without other autoimmune diseases (primary aPL/APS) and aPL-positive SLE patients (SLE aPL/APS). Results: As of January 2018, 105 aPL-positive patients were recruited (mean age: 42.6±10.1 [min-max: 19–70]; 83 [79%] female; and 67 [64%] with another SAID). Ten patients were excluded from the analysis due to their SAID history other than SLE. Of the remaining 95 patients, 38 (40%) had primary aPL/APS; 57 (60%) fulfilled the ACR SLE Classification Criteria; 42 (44%) had thrombotic APS (TAPS) (8 arterial, 24 venous, and 8 both); 21 (22%) had obstetric APS (OAPS); 22 (23%) had both TAPS and OAPS (7 arterial, 14 venous, and 1 both); and 10 (11%) had no TAPS/OAPS. Fifty percent of the patients had history of at least one non-criteria aPL-manifestation. Demographics, clinical and laboratory manifestations, and medications were similar between primary aPL/APS and SLE aPL/APS patients except increased frequency of autoimmune hemolytic anaemia, aCL IgG, and hydroxychloroquine use in SLE aPL/APS patients (table 1). Conclusions: The analysis of our multicenter aPL database demonstrates that the frequencies of thrombosis and pregnancy morbidity are similar between aPL-positive patients with or without SLE. Half of the patients in both groups had history of at least one "non-criteria" aPL-manifestation; only autoimmune hemolytic anaemia was more frequent in aPL-positive patients with SLE. References: [1] Schreiber K, Sciascia S, de Groot PG, Devreese K, Jacobsen S, Ruiz-Irastorza G, et al. Antiphospholipid syndrome. Nat Rev Dis Primers2018;4:17103. [2] Gómez-Puerta JA, Cervera R. Diagnosis and classification of the antiphospholipid syndrome. J Autoimmun2014;48–49:20–5. Disclosure of Interest: None declared